Effects of low-dose aspirin in bipolar disorder: study protocol for a randomised controlled trial (the A-Bipolar RCT) - Maria Faurholt-Jepsen; Maj Vinberg; Lars Vedel Kessing; Julie Lyng Forman; Kamilla Woznica Miskowiak; Klara Coello; Caroline Fussing Bruun; Jeff Zarp (BMJ Open)
Introduction Accumulating data support the association between increased inflammation and bipolar disorder (BD), and preliminary data suggest that augmentation with low-dose aspirin (LDA) may protect against the onset and deterioration of BD via anti-inflammatory pathways. The A-bipolar randomised controlled trial (RCT) aims to investigate whether adding LDA to standard treatment improves day-to-day mood instability (MI) in BD.Methods and analysis A two-arm, triple-blind, parallel-group, superiority RCT including 250 patients with newly diagnosed BD treated at the Copenhagen Affective Disorder Clinic, Denmark. Participants are randomised 1:1 to either 150 mg of acetylsalicylic acid daily (LDA) or a placebo for six months in addition to their regular treatment. Mood instability, calculated from daily smartphone-based mood evaluations, is the primary outcome measure due to its internal validity as a real-life measure for patients and external validity as it reflects patients’ illness severity and functioning. Analyses will be conducted as intention-to-treat analyses using a linear mixed model including time (categorical) and the time–treatment interaction as fixed effects and with an unstructured covariance pattern to account for repeated measurements on each study participant. The trial is Good Clinical Practice monitored.Ethics and dissemination The Danish Research Ethics Committee (H-21014515) and the data agency, Capital Region of Copenhagen (P-2021-576) approved the trial. Results will be published in peer-reviewed journals.Trial registration number NCT05035316.